1997
DOI: 10.1172/jci119123
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin and angiotensin II stimulation of Na+-H+ exchange is impaired in cardiac hypertrophy.

Abstract: We compared the effects of endothelin-1 (ET-1) on intracellular pH, intracellular [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 41 publications
2
37
1
2
Order By: Relevance
“…However, several studies reported that ET-1 showed a reduced or absent PIE in myocardium or isolated myocytes from diseased hearts (15,25,29,31,42,47). Similarly, Pieske et al (31) demonstrated that ET A -mediated PIE is attenuated in end-stage failing human ventricular muscle strips desspite an increase in ET A expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies reported that ET-1 showed a reduced or absent PIE in myocardium or isolated myocytes from diseased hearts (15,25,29,31,42,47). Similarly, Pieske et al (31) demonstrated that ET A -mediated PIE is attenuated in end-stage failing human ventricular muscle strips desspite an increase in ET A expression.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in Na ϩ /H ϩ exchanger activity of cardiac papillary muscle has been reported in streptozotocin-induced diabetic rats (27). A defect in the coupling of PKC signaling with the Na ϩ /H ϩ exchanger has been shown in adult hypertrophied myocardium generated by aortic banding (28). Since PKC␤2 activation was observed in diabetic cardiomyopathy (29), and PKC␤2 overexpression mice had left ventricular hypertrophy (7), we cannot exclude the possibility that regulation of intracellular pH might be impaired in these mice and contribute to diminished cardiomyocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…6,9,10 At 9 to 11 weeks after the surgery, after closed-chest LV pressure was recorded, the animals were euthanized and LV myocytes were prepared with collagenase perfusion by a method described previously. [11][12][13][14] Myocyte [Ca 2ϩ ] i was measured with fluo 3 (Molecular Probes, Inc) with an excitation wave length of 480Ϯ20 nm and emission signal detected at 535Ϯ25 nm. The optical system and calibration method for [Ca 2ϩ ] i are described in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14] The pH i was measured with seminaphthorhodafluor-1 (SNARF 1-AM) (Molecular Probes, Inc) with an excitation wave length of 540 nm and emission signal detected at 580 and 640 nm. 12,13 The pH i for each cell was calibrated in situ by exposing cells to solutions of varying pH and was calculated by the method previously described. 12,13 At baseline, myocytes were superfused with oxygenated HEPESbuffered Tyrode's solution.…”
Section: Methodsmentioning
confidence: 99%